2014
DOI: 10.5114/pg.2014.40851
|View full text |Cite
|
Sign up to set email alerts
|

Functional dyspepsia symptom resolution after Helicobacter pylori eradication with two different regimens

Abstract: IntroductionFunctional dyspepsia (FD), a common functional gastrointestinal disorder, has a complex underlying pathophysiological mechanism that involves changes in gastric motility, visceral hypersensitivity, genetic susceptibility, psychosocial factors and Helicobacter pylori infection. Although there are several H. pylori eradication treatments, there is not enough data that compare these different eradication treatments for FD symptom resolution. Most previous studies have focused on the eradication rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…A total of 27 full articles and conference abstracts were further assessed for eligibility. After exclusion of trials that used modified sequential therapy ( n = 7) and those included paediatric patients ( n = 7), a total of 13 trials including 5173 patients were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 27 full articles and conference abstracts were further assessed for eligibility. After exclusion of trials that used modified sequential therapy ( n = 7) and those included paediatric patients ( n = 7), a total of 13 trials including 5173 patients were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the enrolled trials were shown in Table . Only the trial conducted in Latin America and the trial in Taiwan enrolled asymptomatic subjects in the community .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is Helicobacter pylori infection of the stomach. Numerous studies have addressed the possible pathophysiological mechanisms of functional bowel disorders, despite the unclear etiology of such disorders [14][15][16]. During the past 40 years, many factors that contribute to the pathophysiology of IBS have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…В Турции было проведено рандомизированное слепое контроли-руемое исследование эффективности последова-тельной (1-я группа) и стандартной (2-я группа) тройной антихеликобактерной терапии в разре-шении симптомов функциональной диспепсии. Эрадикация была достигнута у 83,54% пациен-тов из 1-й группы и у 80,4% из 2-й группы, при этом не было выявлено существенного различия в разрешении симптомов функциональной дис-пепсии [42].…”
unclassified